Indonesian Islamic Theology: Understanding Exclusivism, Inclusivism, and Pluralism in the Context of Religious Plurality - Rustriningsih Rustriningsih; Mukhlisin Saad (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
In Indonesia, religious issues have emerged as a subject of intense debate and polemic. Conflicting religious claims often incite debates and hostilities purportedly in the name of faith. In certain instances, the emergence of inter-religious conflicts in Indonesia is exacerbated by exclusionary perspectives on religion. This study aims to critically examine the concept of Islamic theology within the context of Indonesia’s pluralistic society, characterized by its rich religious diversity. Employing a qualitative research methodology with a descriptive-analytical approach, this research utilizes library research to gather a variety of thematic literature. The findings indicate that Indonesia is a nation marked by significant religious plurality. In this context, Islam, as an inherently open faith, embraces inclusivism and pluralism, which serve as essential frameworks for mitigating interfaith conflicts arising from competing religious truth claims. Consequently, the promotion of inclusivist and pluralist perspectives in religion fosters a culture of tolerance, thereby facilitating a harmonious coexistence among adherents of diverse faiths.